A Study of Future Opportunities and Challenges in Digital Healthcare Sector: Cyber security vs. crimes in digital healthcare sector - Avani Rachh (ACHSM, 2021)
Objective: The current study is to understand the opportunities for and challenges faced by digital healthcare sector. The aim of the study is to suggest measures for securing data and information collected by the sector plus have safer online transactions. Design and Setting: The secondary data was collected from reliable sources. The primary data was collected online. The quantitative and qualitative analysis was done on data. The data was statistically analysed for this research article. Results: Even though healthcare sector has spent on digital health and cybersecurity but still the number of cybercrime cases have increased. An attempt is made to understand the factors that can influence the number of cybercrime cases. Conclusion: The healthcare sector has opportunities in the digital healthcare field in the current pandemic situation. At the same time, it has challenges to reduce the cybercrime cases as hackers are stealing confidential data and to take stringent measures to reduce the same.